(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2021)
The article analyzes the curriculum matrices of undergraduate courses in history offered on the campuses of federal universities in Brazil. It aims to analyze how many and which mandatory subjects are specifically in charge of debates on the teaching of history during the initial training of the history teacher in Brazil to understand what content is worked on in the respective subjects. As a methodology, I use the quantitative procedures by which I cataloged the matrices and the disciplines with which I prepared tables and charts with the data. Then I use the qualitative foundations to analyze the content presented in the course plans. The research concludes by pointing out that there is a great diversity of themes and ways of presenting the discussions about the teaching of History with the predominant presence of the methodology content in more than 80% of the analyzed matrices.